The Development of Malay Religious Magazine Publications in Malaysia Post-Independence, 1960-1970 - Kasa, Annuar Ramadhon; Hj. Hamzah, Norhayati; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2024)
Since the early 20th century, magazines have served as pivotal instruments in Islamic outreach, and their development continued to grow after Malaysia’s independence. In this new phase for Malaysia, religious magazines underwent a significant phase of growth, marked by the emergence of various publications produced by different publishing bodies. This expansion was driven by an increasing religious consciousness within the Malay society, encompassing both government and non-government initiatives. However, the documentation and the history of religious magazine publications during this period remain insufficiently explored. Accordingly, this study examines the development of religious magazine publications between 1960 to 1970, highlighting their profiles as well as their content. This qualitative research utilises documentation as its primary data collection method and applies content analysis with an inductive approach to interpret the findings. The study reveals that a total of ten religious magazines were published during this period comprising five published by religious authorities, three by non-governmental Islamic organisations, and two by private and commercial entities. Despite originating from different publishing orientations, all these magazines shared a common objective which is to disseminate Islamic teachings and values through written works, fostering a deeper understanding of Islam and promoting Islamic outreach within the Malay community.